Mesoporous Polydopamine Loaded Pirfenidone Target to Fibroblast Activation Protein for Pulmonary Fibrosis Therapy - Fang, Qi; Liu, Shaoyu; Cui, Jiangyu; Zhao, Ruiyue; Han, Qian; Hou, Peng; Li, Youcai; Lv, Jie; Zhang, Xiaoyao; Luo, Qun; Wang, Xinlu (Frontiers in Bioengineering and Biotechnology, 2022)
Recently, fibroblast activation protein (FAP), an overexpressed transmembrane protein of activated fibroblast in pulmonary fibrosis, has been considered as the new target for diagnosing and treating pulmonary fibrosis. In this work, mesoporous polydopamine (MPDA), which is facile prepared and easily modified, is developed as a carrier to load antifibrosis drug pirfenidone (PFD) and linking FAP inhibitor (FAPI) to realize lesion-targeted drug delivery for pulmonary fibrosis therapy. We have found that PFD@MPDA-FAPI is well biocompatible and with good properties of antifibrosis, when ICG labels MPDA-FAPI, the accumulation of the nanodrug at the fibrosis lung in vivo can be observed by NIR imaging, and the antifibrosis properties of PFD@MPDA-FAPI in vivo were also better than those of pure PFD and PFD@MPDA; therefore, the easily produced and biocompatible nanodrug PFD@MPDA-FAPI developed in this study is promising for further clinical translations in pulmonary fibrosis antifibrosis therapy.